Measure invariance of the Political Skill Inventory (PSI) across five cultures - (:unkn) unknown (My University, 2012)
This research expands the study of political skill, a construct developed in North America, to other cultures. We examine the psychometric properties of the Political Skill Inventory (PSI) and test the measurement equivalence of the scale in a non-American context. Respondents were 1511 employees from China, Germany, Russia, Turkey, and the United States. The cross-cultural generalizability of the construct is established through consistent evidence of multi-group invariance in an increasingly stringent series of analyses of mean and covariance structures. Overall, the study provides systematic evidence that political skill can be treated as a stable construct among diverse cultural groups. Furthermore, our findings demonstrate that translated PSI measures operationalize the construct similarly. With some exceptions, the item loadings and intercepts are invariant for the US and non-US responses, suggesting partial measurement equivalence. After verifying the accuracy of item translation, we conclude that any differences can be explained by variation in the cultural value of uncertainly avoidance and cultural differences on a low-to-high context continuum. Detected dissimilarities are addressed, and some suggestions regarding the correct use across borders of the instrument by managers and researchers are provided. © 2012 The Author(s).
Keywords: China; cross-cultural measure invariance; Germany; political skill inventory; psychometric properties; Russia; soft skills; Turkey; USA